A proposal to Add a Scholarship Unit for Islamic Education Curriculum for third Secondary Students According to Schools Promoting Positive Behavior in View of the Kingdom’s Vision 2030 - Idrees, Najwa Farouk (Journal of Curriculum and Teaching Methodology, 2023)
The aim of the research is to reach a proposal to add a scholarship unit in Islamic education courses for third secondary students according to schools that promote positive behavior in the light of the Kingdom’s vision 2030. The researcher used the descriptive analytical approach. On a sample of (58) male and female secondary school students in Jeddah, and by using the statistical program (SPSS) to process the data, it was concluded that the need of secondary school students to add an educational unit on scholarship within one of the Islamic education curricula came with a high degree. Where the need of the students of the third secondary grade came in the first place, and the degree of awareness of the secondary school students of the scholarship conditions came before adding the proposed unit at an average level, and the degree of awareness of the third grade secondary students came in the first place, with regard to the objectives of teaching the scholarship unit, which is represented in: (loyalty and belonging to the homeland Respect for regulations and laws, preserving religious identity) came at a very high level, and the goal of preserving religious identity came in the first place among the study sample. It was high, and the jurisprudence course ranked first, and the degree of approval of the aspects that should be dealt with by the scholarship unit (religious-social-personal-national) was very high, and the religious aspect came first, and 44.8% of the sample agreed on the name of the unit. Scholarship”, the study presented a set of methods and strategies used to reach the objectives of teaching the unit, and based on the results, the researcher presented a number of recommendations and proposals to add a scholarship unit for third secondary students in line with The Kingdom’s Vision 2030.